Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/sap.0000000000003187
|View full text |Cite
|
Sign up to set email alerts
|

Does Dedicated Research Time During Residency Predict Resident Academic Productivity and a Future Academic Career?

Abstract: Objective Dedicated research time is a component of certain plastic surgery programs, and yet, there is limited research examining its impact on academic productivity and career outcomes. This study aimed to assess the effect of dedicated research time on the academic productivity of residents and the likelihood of pursuing an academic career. Methods We conducted a cross-sectional study that examined bibliometric indices of integrated plastic surgery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We also noted attrition from seminar learners (n ¼ 19) to longitudinal learners (n ¼ 11). As others have found that protecting research time for trainees may be correlated with academic output, 18,19 one potential hypothesis for this discrepancy is that our trainees, who did not have protected time for this elective curriculum may have been limited in their ability to participate because of their clinical workload. Although some residency programs afford flexibility through X þ Y systems, in which residents switch between 4 weeks of an inpatient service followed by 2 to 4 weeks of an elective rotation with flexibility for protected academic time, this may not be true for all residencies or fellowships, particularly procedural subspecialties.…”
Section: Discussionmentioning
confidence: 82%
“…We also noted attrition from seminar learners (n ¼ 19) to longitudinal learners (n ¼ 11). As others have found that protecting research time for trainees may be correlated with academic output, 18,19 one potential hypothesis for this discrepancy is that our trainees, who did not have protected time for this elective curriculum may have been limited in their ability to participate because of their clinical workload. Although some residency programs afford flexibility through X þ Y systems, in which residents switch between 4 weeks of an inpatient service followed by 2 to 4 weeks of an elective rotation with flexibility for protected academic time, this may not be true for all residencies or fellowships, particularly procedural subspecialties.…”
Section: Discussionmentioning
confidence: 82%
“…The mean number of publications post-training was significantly higher than the mean while training. Several different reasons could account for this but when asked, residents have listed lack of time, insufficient research skills, the intensity of clinical duties, financial support, and inadequate mentorship as the major barriers to project completion [ 4 , [14] , [15] , [16] ]. Due to a growing pressure to increase clinical activities, more than half of surgeons report spending <20 % of their efforts on research creating a visible lack of modeling and mentorship within programs for residents [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies that demonstrated that applicants with completed research fellowships were more likely to match into plastic surgery, partially due to a greater number of publications. [16][17][18] However, fewer people from the indirect pathway group completed a research year. This is also consistent with the fact that independent residency applicants tend to have fewer preresidency publications.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Older plastic surgery match literature demonstrated that successful match rates were associated with Alpha Omega Alpha status and graduating from a top-40 ranked medical school. 14,18,19,31,32 This is likely due to the fact that medical schools not ranked in the top 40 provided poorer exposure to plastic surgery. Stoehr et al looked at residency pathways taken by current plastic surgery residents in the United States, focusing on the routes taken by those residents who were unsuccessful in their initial efforts to match.…”
Section: Discussionmentioning
confidence: 99%